Cerebrospinal fluid interleukin-6 is a potential diagnostic biomarker for central nervous system involvement in adult acute myeloid leukemia - Gu, Jiayan; Huang, Xin; Zhang, Yi; Bao, Chenhui; Zhou, Ziyang; Tong, Hongyan; Jin, Jie (Frontiers in Oncology, 2022)
Objective: We evaluated the correlation between cerebrospinal fluid (CSF) cytokine levels and central nervous system (CNS) involvement in adult acute myeloid leukemia (AML). Methods: The study sample consisted of 90 patients diagnosed with AML and 20 with unrelated CNS involvement. The AML group was divided into two sub-groups: those with (CNS+, n=30) and without CNS involvement (CNS-, n=60). We used a cytometric bead assay to measure CSF interleukin (IL)-2, -4, -6, and -10, tumor necrosis factor-α, interferon-γ, and IL-17A. We used receiver operating characteristic curves to evaluate the ability of CSF cytokine levels to identify CNS involvement in adult AML. Results: CSF IL-6 levels were significantly higher in CNS+adult AML patients and positively correlated with the lactate dehydrogenase levels (r=0.738, p<0.001) and white blood cell (WBC) count (r=0.455, p=0.012) in the blood, and the protein (r=0.686, p<0.001) as well as WBC count in the CSF (r=0.427, p=0.019). Using a CSF IL-6 cut-off value of 8.27 pg/ml yielded a diagnostic sensitivity and specificity was 80.00% and 88.46%, respectively (AUC, 0.8923; 95% CI, 0.8168–0.9678). After treating a subset of tested patients, their CSF IL-6 levels decreased. Consequently, the elevated CSF IL-6 levels remaining in CNS+ adult AML patients post-treatment were associated with disease progression. Conclusion: CSF IL-6 is a promising marker for the diagnosis of adult AML with CNS involvement and a crucial dynamic indicator for therapeutic response.